Diagnosis and management of febrile children using the WHO/UNICEF guidelines for IMCI in Dhaka, Bangladesh - Factor S.H; Schillinger J.A; Kalter H.D; Saha S.; Begum H.; Hossain A.; Hossain M.; Dewitt V.; Hanif M.; Khan N.; Perkins B.; Black R.E; et al. (The World Health Organization, 2001)
OBJECTIVE: To determine whether the fever module in the WHO/UNICEF guidelines for the integrated management of childhood illness (IMCI) identifies children with bacterial infections in an area of low malaria prevalence. METHODS: Physicians assessed a systematic sample of 669 sick children aged 2-59 months who presented to the outpatient department of Dhaka Shishu Hospital, Bangladesh. FINDINGS: Had IMCI guidelines been used to evaluate the children, 78% of those with bacterial infections would have received antibiotics: the majority of children with meningitis (100%), pneumonia (95%), otitis media (95%) and urinary tract infection (83%); and 50% or less of children with bacteraemia (50%), dysentery (48%), and skin infections (30%). The current fever module identified only one additional case of meningitis. Children with bacteraemia were more likely to be febrile, feel hot, and have a history of fever than those with dysentery and skin infections. Fever combined with parental perception of fast breathing provided a more sensitive fever module for the detection of bacteraemia than the current IMCI module. CONCLUSIONS: In an area of low malaria prevalence, the IMCI guidelines provide antibiotics to the majority of children with bacterial infections, but improvements in the fever module are possible.